The Impact Of The Arbitration Clause On The Judicial Immunity Of The State - علي, غسان; صبح , عواطف (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aims to investigate the issue of the state's judicial immunity as a problem in itself, specifically in relation to foreign investment contracts and disputes that arise between their parties and their resort to arbitration. The general character of the state as a party to arbitration and its enjoyment of judicial immunity in the face of submission to the national judiciary necessitates dealing with it with great caution and granting it preferential treatment by the authorities of other countries because of the disturbance that this treatment may cause in international relations. This study relied on the descriptive and analytical method and research on the most prominent articles and legal researches that dealt with the subject of the study. And I reached many results, the most prominent of which are: the balance must be achieved between the concepts of the public interest of the state and the achievement of its sovereignty, and the protection of its interests, and also to achieve the interest of the contracting parties in investment contracts in a manner that does not affect the sovereignty of the state through the adoption of the arbitration clause that is based on the will and satisfaction of the contracting parties. The necessity of international interaction between countries in light of the tremendous economic developments imposed the necessity of organizing the issue of judicial immunities for states and finding solutions to the state’s adherence to its judicial immunity in exchange for compliance with the prudent condition in the event of disputes, but the necessity of international cooperation requires states to provide facilities to attract investments and in return they can request guarantees. From investors before the national judiciary of a country to conclude an investment contract, to carry out their activity.